2005
DOI: 10.1074/jbc.m509352200
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 4 Signaling Regulates Cytosolic Phospholipase A2 Activation and Lipid Generation in Lipopolysaccharide-stimulated Macrophages

Abstract: Inflammatory lipid mediators such as prostaglandins and leukotrienes play crucial roles in the pathogenesis of bacterial lipopolysaccharide (LPS)-induced inflammation. Cytosolic phospholipase A 2 (cPLA 2 ) is a key enzyme in the generation of pro-inflammatory lipid mediators. Here, we found that Toll-like receptor 4 (TLR4) is essential for LPS-induced cPLA 2 activation and lipid release. Inhibition of TLR4 protein expression by TLR4 small interfering RNA or neutralization of TLR4 by the specific antibody again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
94
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 65 publications
14
94
2
1
Order By: Relevance
“…We and others have shown in monocytes and macrophages that cPLA 2 ␣ phosphorylation might be caused by various MAPKs (39,95). We found here that HA-induced cPLA 2 ␣ activation is associated with ERK1/2, p38, and JNK activation (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…We and others have shown in monocytes and macrophages that cPLA 2 ␣ phosphorylation might be caused by various MAPKs (39,95). We found here that HA-induced cPLA 2 ␣ activation is associated with ERK1/2, p38, and JNK activation (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…3, B and C). Interestingly, the time course of ERK1/2 phosphorylation was different from other studies showing TLR4 involvement (39,96). Even though the peak phosphorylation of all three MAPKs was at 30 min, ERK1/2 phosphorylation tended to be sustained up to 6 h, both in murine macrophages and in human monocytes (Fig.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…19-HETE and prostanoids PGE 2 and PGF 2α are proinflammatory metabolites of AA; both prostanoids are produced from COX-2 and the subsequent action of specific inducible prostanoid synthases (40). Pretreatment with simvastatin or dLGG were characterized most significantly by the elevated levels of LXA 4 in the liver, while dLGG posttreatment can also increase EPA metabolites, resolvin D1 and 15-HEPE, and DHA and its metabolites, 17-HDoHE, 10,17-DiHDoHe.…”
Section: Resultsmentioning
confidence: 99%
“…34 The MyD88-dependent pathway of LPS-TLR4 signaling was found to activate MAPKs, including extracellular signal-regulated kinase, p38 and c-Jun N-terminal kinase, with p38 being thought to be required for LPS-induced activation of cPLA 2 and lipid release. 25 MyD88-deficient mice show resistance to LPS-induced responses, including cytokine production by macrophages, and MyD88 − / − macrophages do not produce IL-6 in response to LPS. 35 Consistent with these previous observations, we found that transfection of Raw 264.7 cells with MyD88 siRNA inhibited LPS-induced p38 MAPK phosphorylation (Figure 6a) and that the p38-specific inhibitor SB203580 attenuated the LPS-induced phosphorylation of cPLA 2 and upregulation of IL-6 mRNA (Figures 6b and c).…”
Section: Nox1-ros Signaling Functions Downstream Of Blt2 In Lpsinducementioning
confidence: 99%